2004
DOI: 10.1086/424868
|View full text |Cite
|
Sign up to set email alerts
|

Dense, Ionized, and Neutral Gas Surrounding Sagittarius A*

Abstract: We present high resolution H41α hydrogen recombination line observations of the 1.2 ′ (3 pc) region surrounding Sagittarius A ⋆ (Sgr A ⋆) at 92 GHz using the Millimeter Array at the Owens Valley Radio Observatory (OVRO) with an angular resolution of 7 ′′ × 3 ′′ and velocity resolution of 13 km s −1. New observations of H31α, H35α, H41α and H44α lines were obtained using the NRAO 12-m telescope, and their relative line strengths are interpreted in terms of various possible emission mechanisms. These NRAO 12-m m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 45 publications
6
41
3
Order By: Relevance
“…Because radio recombination lines at centimeter wavelengths can be dominated by stimulated emission and affected by pressure broadening, Shukla et al (2004) observed the Sgr A West region in the 92 GHz (3.3 mm) H41α recombination line. At this higher frequency, the continuum and recombination-line emissions are believed to arise mostly in denser ionized gas.…”
Section: The Central Cavitymentioning
confidence: 99%
See 3 more Smart Citations
“…Because radio recombination lines at centimeter wavelengths can be dominated by stimulated emission and affected by pressure broadening, Shukla et al (2004) observed the Sgr A West region in the 92 GHz (3.3 mm) H41α recombination line. At this higher frequency, the continuum and recombination-line emissions are believed to arise mostly in denser ionized gas.…”
Section: The Central Cavitymentioning
confidence: 99%
“…On the other hand, little molecular gas seems to be present, except possibly for a hot and dense molecular component detected in NH 3 (6, 6) emission very near Sgr A * (Herrnstein & Ho 2002). The general lack of molecular gas can be understood if any initially molecular cloud inside the central cavity has been largely photo-dissociated by the intense ambient UV radiation (Jackson et al 1993;Latvakoski et al 1999;Shukla et al 2004).…”
Section: The Central Cavitymentioning
confidence: 99%
See 2 more Smart Citations
“…The gas is moving in circular orbits, rotating around the nucleus with a velocity of 110 km s −1 (Liszt et al 1985;Marr et al 1993), but it also presents noncircular motions (e.g. : Güsten et al 1987;Jackson et al 1993;Marshall et al 1995;Shukla et al 2004;Christopher et al 2005). The CND does not appear to be an equilibrium structure.…”
Section: Introductionmentioning
confidence: 99%